Iqbāl aur Sayyid Sulaimān Nadvī - T̤āhir Taunsvī (Maktabah-yi ʻĀliyah, 1977)
Correspondence exchanged between Sir Muhammad Iqbal, 1877-1938, the national poet of Pakistan, and Syed Sulaiman Nadvi, d. 1953, famous muslim scholar.